2014
DOI: 10.1371/journal.pone.0092887
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction in Gulf War Illness Revealed by 31Phosphorus Magnetic Resonance Spectroscopy: A Case-Control Study

Abstract: BackgroundApproximately 1/3 of 1990-1 Gulf War veterans developed chronic multisymptom health problems. Implicated exposures bear mechanisms that adversely affect mitochondria. Symptoms emphasize fatigue, cognition and muscle (brain and muscle are aerobically demanding); with protean additional domains affected, compatible with mitochondrial impairment. Recent evidence supports treatments targeting cell bioenergetics (coenzyme10) to benefit Gulf War illness symptoms. However, no evidence has directly documente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
67
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 30 publications
8
67
0
Order By: Relevance
“…There is some evidence that mitochondrial disturbances might be present in veterans with GWI. A small matched case-control study of 31 Phosphorus Magnetic Resonance Spectroscopy showed that veterans with GWI had prolonged post-exercise recovery of muscle phosphocreatine following exercise compared to controls, suggesting defective energy metabolism in the mitochondria (Koslik et al, 2014). As mentioned above, a fMRI study showed impaired lactate utilization as an alternative energy supply in the brains of veterans with GWI (Rayhan et al, 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that mitochondrial disturbances might be present in veterans with GWI. A small matched case-control study of 31 Phosphorus Magnetic Resonance Spectroscopy showed that veterans with GWI had prolonged post-exercise recovery of muscle phosphocreatine following exercise compared to controls, suggesting defective energy metabolism in the mitochondria (Koslik et al, 2014). As mentioned above, a fMRI study showed impaired lactate utilization as an alternative energy supply in the brains of veterans with GWI (Rayhan et al, 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…Noncompliance is a possibility: participants are veterans with CNS problems, and both cognitive and mood problems have been shown to predict medication noncompliance (Stilley, Sereika, Muldoon, Ryan, & Dunbar-Jacob, 2004). Barriers to assimilation may be present in some; gastrointestinal problems such as diarrhea are not uncommon in GWI, and pancreatic exocrine dysfunction can accompany mitochondrial problems (Hsu et al, 2005), which is reported in GWI (Koslik, Hamilton, & Golomb, 2014). At least one participant acknowledged having disregarded instructions to take one softgel from the smaller bottle or allotment and two daily from the larger, mixing all together.…”
Section: Discussionmentioning
confidence: 99%
“…43 Recent findings from Beatrice Golcomb’s group 44 provide empirical support for a role of mitochondrial dysfunction and oxidative stress, which promotes and is caused by mitochondrial dysfunction, 45 in GWI. With respect to this finding, it is noteworthy that sleep pathology is a known complication of mitochondrial dysfunction, possibly because cellular energy failure causes both central neurological and peripheral neuromuscular degenerative changes that commonly present as central sleep apnea and poor ventilatory response to hyperapnea.…”
Section: Discussionmentioning
confidence: 99%